Transformational and Transactional Leadership Styles of Nurse Managers and Job Satisfaction among Filipino Nurses: A Pilot Study - Tuppal, Cyruz P; Loo, Bradley Goldie K; Abe, Kenji Hennessy C.; LapeÃ±a, Lucky Fitzgerald R (Nurse Media Journal of Nursing, 2017)
Background: Due to the paucity of literature in leadership styles and job satisfaction within the Philippine context, this descriptive correlational study among Filipino nurses (FNs) was piloted in a selected tertiary hospital in Manila.Purpose: This study utilized a descriptive correlational research design to describe aspects of a situation and explore relationships among leadership styles and job satisfaction, without seeking to establish causal connectionsMethods: Before the data collection, the researchers secured an administrative and ethical clearance from the executive assistant to the President thru the Officer-in-Charge of the Nursing Service Division of the hospital. There were 285 staff nurses, of which only 100 nurses were qualified to have at least one year of experience. Three sets of questionnaires were disseminated, and responses were treated analyzed using the descriptive statistics to describe the demographic and work profile, LS, and JS while Pearson R correlation was used to measure the relationship between LS and JS.Results: Using self-administered questionnaires, FNs rated their level of satisfaction (M=3.37) from high to a moderate extent along with professional autonomy (M=3.91), work environment (M=3.81), work assignment (M=3.61), and benefits (M=2.71). Participants agreed that their nurse managers utilized either transformational or transactional leadership styles. Findings indicate that transformational (r=0.558, p<0.000) and transactional (r=0.528, p< 0.000) leadership styles of nurse managers were correlated to nursesâ€™ job satisfaction.Conclusion: The finding explicates that FNs were satisfied in their professional autonomy, work environment, and work assignment but moderately satisfied in work benefits which were also apparent in the global literature. Furthermore, the results indicate that leadership styles are related to the overall job satisfaction of among nurses.